Utilizing fine coal waste as a topsoil substitute on mine reclamation - Wahyu Sriningsih; Iskandar Iskandar; Dyah Tjahyandari Suryaningtyas (Journal of Degraded and Mining Lands Management, 2022)
Topsoil in post-mined land generally has a low fertility level. Its availability is not always in sufficient quantities to meet minimal needs for mine reclamation, so substitute materials and ameliorants are needed to increase its quantity and quality. Fine coal and fly ash-bottom ash (FABA) are wastes expected to reduce the demand for topsoil and, at the same time, may improve topsoil quality. This study aimed to examine the application of fine coal as a topsoil substitution and its effect on changes in the chemical properties of topsoil and the growth of jabonv (Anthocephalus chinensis). The study was conducted in a greenhouse with a completely randomized design model with two factors. The first factor was fine coal with four levels of 0, 10, 20, and 50% from the topsoil (w/w), and the second factor was FABA with three levels of 0, 500, 1000 g/15 kg of growing media. The jabon plant was grown for 24 weeks. The results showed that up to 50% fine coal could be used as a topsoil substitution. The interaction of fine coal and FABA increase pH, organic C, total N, cation exchange capacity, available P, base saturation, exchangeable cations, and micronutrients, and reduce the amount of exchangeable Al in the soil. FABA with a dose of 1000 g/15 kg of growing media and 50% fine coal was the best treatment to increase the growth of the jabon plant.